Hubungan di Antara Faktor Demografi dengan Penentuan Kadar Hantaran: Kajian di Perlis, Kedah, Pulau Pinang Dan Perak - Azahari, Raihanah; Saripudin, Khairun Najmi; Abd Wahab, Raihana (Jurnal Fiqh, 2009)
This article focuses on the issue of hantaran according to the practice by Malay muslim community in Malaysia. The aim of the study is to identify relations between demografic factor such as level of education, education background and the income with the rate of the hantaran. This article also try to identify the relevance rate of hantaran which will be implemented by the community nowadays. To collect the data, methods of library research and questionnaire survey were used. Data from the questionnaire were prosesed by using SPSS 12. Two type of statistics have been used to describe the data into frequency, percentage, crosstabulation and chi-square. Result shows that only the level of education and education background was significance correlatively to determine high or low rate of the hantaran.